2008
DOI: 10.1002/chem.200701990
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Threefold Symmetry in Asymmetric Catalysis: The Case of Tris(oxazolinyl)ethanes (“Trisox”)

Abstract: Rotational molecular symmetry, modularity and other aspects of ligand design have played a role in the development of a new class of stereodirecting ligands. The use of highly symmetrical, stereodirecting ligands may reduce the number of transition states and diastereomeric reaction intermediates and, in favourable cases, this degeneration of alternative reaction pathways may lead to high stereoselectivity in catalytic reactions and greatly simplifies the analysis of such transformations. In this concept artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 105 publications
0
27
0
Order By: Relevance
“…[2] We found that this spontaneous resolution was approximately 80 % effective for the trivalent cations Y, Er and Eu, from the smaller half of the lanthanides. Specifically, treatment of LnN'' 3 (N'' = NA C H T U N G T R E N N U N G {SiMe 3 } 2 ) with three equivalents of rac-HL 1 generates isomers of [Ln(L 1 ) 3 ], in which 80 % of the mixture comprises the two enantiomers (RRR)-[Ln(L 1 ) 3 ] and (SSS)-[Ln(L 1 ) 3 ], and the remaining 20 % is composed of (RRS)-[Ln(L 1 ) 3 ] and (SSR)-[Ln(L 1 ) 3 ]. To our knowledge, this represented the only example of spontaneous resolution of three molecules of a racemic ligand at a single lanthanide centre.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] We found that this spontaneous resolution was approximately 80 % effective for the trivalent cations Y, Er and Eu, from the smaller half of the lanthanides. Specifically, treatment of LnN'' 3 (N'' = NA C H T U N G T R E N N U N G {SiMe 3 } 2 ) with three equivalents of rac-HL 1 generates isomers of [Ln(L 1 ) 3 ], in which 80 % of the mixture comprises the two enantiomers (RRR)-[Ln(L 1 ) 3 ] and (SSS)-[Ln(L 1 ) 3 ], and the remaining 20 % is composed of (RRS)-[Ln(L 1 ) 3 ] and (SSR)-[Ln(L 1 ) 3 ]. To our knowledge, this represented the only example of spontaneous resolution of three molecules of a racemic ligand at a single lanthanide centre.…”
Section: Introductionmentioning
confidence: 99%
“…A few examples of ligand self-recognition based solely on chirality exist in transition-metal chemistry and have helped define the requirements for ligand self-recognition: [3][4][5][6][7][8][9][10] Ligands must be rigid, sized to fit the correct number around the metal centre (here 2 or 3), project chir-Abstract: The reaction of a chiral racemic bidentate ligand HL 1 (tBu 2 P(O)CH 2 CHA C H T U N G T R E N N U N G (tBu)OH) with mid to late trivalent lanthanide cations affords predominantly homochiral lanthanide complexes (RRR)-[Ln(L 1 ) 3 ] and (SSS)-[Ln(L 1 ) 3 ]. A series of reactions are reported that demonstrate that the syntheses are under thermodynamic control, and driven by a ligand self-recognition process, in which the large asymmetric bidentate L 1 ligands pack most favourably in a C 3 geometry around the lanthanide cation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By changing to the Ph-BOX L1 ligand, the desired product was obtained in 76 % yield with 48 % ee (Table 1, entry 1). With the insight gained from our previous work on asymmetric reactions with oxazo-line ligands, [6,7] we expected the substituents on the bridging carbon center to have aprofound effect on the configuration of the oxazoline group,thus affecting the acidity of the Lewis acid when coordinated. When the sidearm-modified BOX (SaBOX)ligand [7] L2,bearing abenzyl group was employed, the ee value increased to 62 %(entry 2).…”
mentioning
confidence: 99%
“…With the insight gained from our previous work on asymmetric reactions with oxazo-line ligands, [6,7] we expected the substituents on the bridging carbon center to have aprofound effect on the configuration of the oxazoline group,thus affecting the acidity of the Lewis acid when coordinated. When the sidearm-modified BOX (SaBOX)ligand [7] L2,bearing abenzyl group was employed, the ee value increased to 62 %(entry 2). However,nofurther improvement was achieved with the SaBOX ligands L3 and L4 (entries 3a nd 4), so we turned to ligands with other substituents,such as alkyl groups.Whenthe ligand L5,having ac yclopropane on the bridging carbon center was used, the ee value decreased to 45 %( entry 5), while the ethyl-substituted ligand L6 led to the desired product in 64 % ee and 75 % yield (entry 6), thus showing astrong influence of the Thorpe-Ingold effect of the ligand on the enantioselectivity.T hus,we changed the Et group to iPr (L7)a nd it led to an increase of the ee value (entry 7).…”
mentioning
confidence: 99%